Education on Knowledge and Attitudes about Smoking Behavior among Adolescent Boys in Junior High School - Wijaya, Dian Rezki; Darwin, Nurul Khaerah; Farhansyah, Muhammad; Thalib, Mutiara; Laelah, Nur (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2024)
Tobacco is a threat to the health of the world's population, with approximately 8 million people dying from tobacco-related causes. Every year, more than 7 million people die from direct tobacco consumption and about 1.2 million people die from second-hand smoke and exposure to tobacco smoke. The purpose of this service is to increase the level of knowledge and attitudes of young men about smoking behavior at SMPN 3 Gowa. The method used is the lecture method and providing posters containing smoking behavior. The target of this activity is young men of SMPN 3 Gowa Regency as many as 30 students. The results of the service showed an increase in the level of knowledge and attitudes of students about smoking behavior It is hoped that the school will have an educational program such as a seminar where students actively participate to exchange opinions or ask directly about smoking behavior. In addition, conduct anti-smoking campaigns in the school environment, put up posters about smoking behavior and involve the role of parents in supervising students.